PENERAPAN DATABASE PRODUK FRANCHISE YOURTEA DENGAN MICROSOFT OFFICE ACCESS - Nurizkita, Najwa Anjani; Putri, Nisma Ardita; Sofyan, Arsya Rinaya; Siregar, Widyadhana Putri; Ananda, Lutfia; Nugraha, Mochammad Raditya; Azizia, Namirah; Irawan, Suhendi (Forum Komunikasi Dosen, 2024)
All businesses today are expanding their business in the era of globalization in terms of products, sales, and data management. It is important for companies to manage data effectively and efficiently. The purpose of this study is to analyze the effectiveness of implementing the Microsoft Access database in managing data in one example of a beverage franchise, namely the Yourtea franchise. Aspects of the business such as, marketing, production, and warehousing will be affected by how well the company manages data and how long the data will last. Data such as beverage types, prices, and stock can be organized precisely and efficiently through the use of Microsoft Access database system. Make it easy for employees to manage product data with features such as Query and data input forms